Evolution of the Banking System in Lithuania: from State-Owned Mono-Banks to a Modern Banking System (1988-2004) - Čičinskas, Jonas; Šadžius, Linas (Ekonomika, 2006)
The creation of a modern banking system in a post-command economy is the subject of this article. The case of Lithuania is investigated throughout the time period of 1988-2004, which is divided into four periods: genesis, early stage, crisis period, and late stage. The substantiality and importance of experience accumulation and learning is shown as a considerable factor of the system building. The initial part is intended to provide some broader, although brief characteristics of the environment in which the new banking system of Lithuania was emerging. The second part provides the chronological process of events in the area. An attempt of periodization of systemic economic reforms is presented in the third part. The final chapter contains some conclusions.